A select group of perpetrators of domestic violence: evidence of decreased metabolism in the right hypothalamus and reduced relationships between cortical/subcortical brain structures in position emission tomography - George, David T; Rawlings, Robert R; Williams, Wendol A; Phillips, Monte J; Fong, Grace; Kerich, Michael; Momenan, Reza; Umhau, John C; Hommer, Daniel (Psychiatry research, 2004)
In an earlier study, we reported that some perpetrators of domestic violence evidenced exaggerated fear-related responses to the panicogenic agent sodium lactate. In the current study, we employed positron emission tomography (PET) to investigate our hypothesis that there are differences in the neural structures and/or pathways that mediate and control the expression of fear-induced aggression in perpetrators of domestic violence. Regional cerebral glucose metabolism was measured in eight male perpetrators of domestic violence who fulfilled DSM-III-R criteria for alcohol dependence (DV-ALC), 11 male participants who fulfilled DSM-III-R criteria for alcohol dependence and had no history of interpersonal aggression (ALC) and 10 healthy male participants who did not fulfill criteria for any DSM-III-R axis I diagnosis and had no history of interpersonal aggression (HCS). DV-ALC had a significantly lower mean glucose uptake in the right hypothalamus compared to ALC and HCS. Correlations were performed between measures of glucose utilization in the brain structures involved in fear-induced aggression. The comparison of DV-ALC to HCS and to ALC differed in six and seven comparisons, respectively, involving various cortical and subcortical structures. HCS and ALC differed between the left thalamus and the left posterior orbitofrontal cortex. These PET findings show that some perpetrators of domestic violence differ from control participants in showing lower metabolism in the right hypothalamus and decreased correlations between cortical and subcortical brain structures. A possible psychological covariate of these changes in regional activity might be fear-induced aggression, but this hypothesis should be examined in larger study groups that undergo provocation during imaging.